Dispute Settlement in Sharia Banking in Indonesia - Syaifuddin Syaifuddin (Randwick International of Social Science Journal, 2023)
The birth of the dual banking system in Indonesia was marked by the establishment of Indonesia's first sharia commercial bank, Bank Muamalat. The first amendments to the Religious Courts Act of 1989 were seen as a response to dispute resolution, but the advent of the law did not immediately open an opportunity for dispute resolution, due to the National Sharia Council and banking fatwas. Indonesian regulations continue to treat disputes in the sharia banking industry as arbitrators, and Law No. 21 of 2008 on Sharia Banking Regulation is another legislative instrument that provides channels for Islamic banking disputes through litigation and out-of-court proceedings. This study was conducted normatively, using different legal materials depending on the issue. The study found that forms of Islamic banking consist of profit products and social and religious products. For charitable sharia banking products, disputes with bank customers can be resolved by national sharia arbitration courts and judicial institutions, whereas social and religious sharia banking products can only be resolved by religious courts or district courts. At the discretion of the judge according to the contract. In the case of disputes between banks and customers, the arbitration board only has the power to decide the dispute and not to enforce the law, but in sharia banks, disputes in litigation, religious courts and district courts have jurisdiction for dispute resolution. Have the right Enforcement where principal or the losing party does not act voluntarily to decide or enforce and/or where the auction leads to legal proceedings.